Perspective creative 02 two point perspective - Rani, Ruzaimi Mat (Singapore Words & Visuals Press Pte Ltd, 2012)
"To sketch well is not necessarily an inherent talent that one needs to be born with; rather, it is a skill that can be learned through many techniques. One of them is the easily acquired perspective setting techniques.

The purpose of this book is to share, in a creative way, the knowledge on perspective setting sketching technique. The main core of this technique is the imaginary box concept which can be learned by many, from basic to creative level. This book is suitable for everyone with basic perspective knowledge and skills.

The book explains the processes of various sketches produced from the same perspective creative settings. The detailed processes of these sketching compositions are animated in demonstrative videos (demo videos) which are available at http://freedrawinglessons.blogspot.com. Feel free to visit to learn more of this interesting perspective creative setting."--
1.0 Introduction--
1.1 Sketching two-point perspective--
1.2 What is perspective creative--
1.3 Basic perspective--
1.4 Perspective creative setting--
2.0 Perspective setting 1--
2.1 Object 1--
2.2 Object 2--
2.3 Exterior space 1--
2.4 Exterior space 2--
2.5 Urban space 1--
2.6 Urban space 2--
2.7 Landscape space 1--
2.8 Landscape space 2--
2.9 Landscape space 3--
2.10 Landscape space 4--
3.0 Perspective setting 2--
3.1 Object 1--
3.2 Object 2--
3.3 Interior space 1--
3.4 Interior space 2--
3.5 Exterior space 1--
3.6 Exterior space 2--
3.7 Exterior space 3--
3.8 Exterior space 4--
3.9 Urban space 1--
3.10 Urban space 2--
4.0 Perspective setting 3--
4.1 Interior space 1--
4.2 Interior space 2--
4.3 Interior space 3--
4.4 Interior space 4--
4.5 Exterior space 1--
4.6 Exterior space 2--
4.7 Exterior space 3--
4.8 Exterior space 4--
4.9 Urban space 1--
4.10 Urban space 2--
Includes bibliographical references
Keywords: Architectural drawing; Perspective